Intensi Berinvestasi Mahasiswa Fakultas Ekonomi Undiksha di Bursa Efek Indonesia - I Gede Aris Widnyana Pratama; Lulup Endah Tripalupi Lulup Endah Tripalupi (Universitas Pendidikan Ganesha, 2022)
The aim of this study is to discover the investing intention of Economics Faculty’s students in Undiksha on the Indonesia Stock Exchange. The type of this study is descriptive research which utilized a qualitative approach in order to describe the investing intention of students in the Indonesia Stock Exchange. The population of this study was all students class in 2017-2020 of Economics Faculty of Undiksha, by using 350 respondents as the samples that were conducted by using the Slovin formula, and sampling techniques using proportional stratified random sampling. The data was collected using questionnaires, and analyzed by descriptive. The result of this study showed that the investing intentions of students from attitude deminsion obtained score of 9,941 falls into the high category. The behavior control dimension obtained a score of 8,096, belonging to the high category. Meanwhile, the subjective norm dimension scored 6,954 in the moderate category. So, it can be concluded that the intention of investing in students is relatively high reviewed from dimension of attitude and behavior control, and the dimension of subjective norm including moderate category.